A SOCIAL DIVISION OF RESPONSIBILITY FOR HEALTH - Kniess, Johannes (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
When is it fair that some people are less healthy than others due to their own individual choices and preferences? In this paper, I explore two alternative answers. The first is a luck-egalitarian account that holds people responsible for choices that society could have reasonably expected them to avoid. I argue that this account is indeterminate and go on to sketch an alternative proposal based on Rawls’s idea of a “social division of responsibility.” This latter approach connects the notion of responsibility for health to the social conditions under which health-related behaviour is developed.